Non-contrast transcatheter aortic valve implantation for patients with aortic stenosis and chronic kidney disease: a pilot study - Freire, Antônio Fernando Diniz; Nicz, Pedro Felipe Gomes; Ribeiro, Henrique Barbosa; Filippini, Filippe Barcellos; Accorsi, Tarso Duenas; Liberato, Gabriela; Nomura, Cesar Higa; Cassar, Renata de Sa; Vieira, Marcelo Luiz Campos; Mathias, Wilson; Pomerantzeff, Pablo Maria Alberto; Tarasoutchi, Flavio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Acute kidney injury (AKI) is frequently observed after transcatheter aortic valve implantation (TAVI). Of note, it is associated with a threefold increase in all-cause and cardiac death. We propose a new non-contrast strategy for evaluating and performing the TAVI procedure that can be especially valuable for patients with aortic stenosis (AS) and chronic kidney disease (CKD) to prevent AKI. Methods Patients with severe symptomatic AS and CKD stage ≥3a were evaluated for TAVI using four non-contrast imaging modalities for procedural planning: transesophageal echocardiogram (TEE), cardiac magnetic resonance, multidetector computed tomography (MDCT), and aortoiliac CO2 angiography. Patients underwent transfemoral (TF) TAVI using the self-expandable Evolut R/Pro, and the procedures were guided by fluoroscopy and TEE. Contrast MDCT and contrast injection at certain checkpoints during the procedure were used in a blinded fashion to guarantee patient safety. Results A total of 25 patients underwent TF-TAVI with the zero-contrast technique. The mean age was 79.9 ± 6.1 years, 72% in NYHA class III/IV, with a mean STS-PROM of 3.0% ± 1.5%, and creatinine clearance of 49 ± 7 ml/min. The self-expandable Evolut R and Pro were implanted in 80% and 20% of patients, respectively. In 36% of the cases, the transcatheter heart valve (THV) chosen was one size larger than the one by contrast MDCT, but none of these cases presented adverse events. Device success and the combined safety endpoint (at 30 days) both achieved 92%. Pacemaker implantation was needed in 17%. Conclusion This pilot study demonstrated that the zero-contrast technique for procedural planning and THV implantation was feasible and safe and might become the preferable strategy for a significant population of CKD patients undergoing TAVR. Future studies with a larger number of patients are still needed to confirm such interesting findings.